Determination of the seroprevalence of Leptospira in cattle by MAT and ELISA - Ertas, HB; Çetinkaya, B; Muz, A; Öngör, H; Özdemir, V; Yazicioglu, N (Scientific Technical Research Council Turkey, 2002)
In this study, 275 serum samples collected from cattle at various ages and of both sexes, slaughtered at state or private abattoirs in Elazig. Malatya and Diyarbakir were examined by MAT and ELISA for the presence of antibodies against Leptospira species. In the serological analysis, using antigens prepared from reference Leptospira hardjo, L. pomona. L. grippotyphosa, L. hebdomadis. and L. icterohaemorrhagiae cultures. 44 (16%) and 64 (23.3%) of the samples were determined to be positive with MAT and ELISA, respectively.
Si?irlarda leptospira seroprevalansinin mikroskopik aglutinasyon testi (MAT) ve ELISA ile saptanmasi
Keywords: Leptospira; MAT; ELISA; cattle